Analisis Motivasi Pinjaman Nasabah Pada Rentenir Berdasarkan Prinsip Pembiayaan Syariah - Nina, Septi Ayu Triten; Pratama, Versiandika Yudha (Department of Islamic Banking, Faculty of Islamic Economics and Business, Institut Agama Islam Negeri Pekalongan, 2021)
This study aims to analyze the motivation of customer loans to moneylenders based on Islamic financing principles.This study is a qualitative descriptive. The type of data used in this study is the primary data with data collection techniques are observation and interviews. The results of this study indicate that the motivation of customers in making loans to moneylenders is due to the need and available facilitie, and the ease of making a loans. In addition, customer knowledge about interest is very low. And than, based on the principles of sharia financing, the transaction pattern is not in accordance with sharia principles because of the customer's ignorance regarding the transaction process.